Automated program repair can relieve programmers from the burden of manually fixing the ever-increasing number of programming mistakes:Automated Program Repair. - GOUES, CLAIRE LE; PRADEL, MICHAEL; ROYCHOUDHURY, ABHIK (Communications of the ACM, 2019)
The article discusses the advantages of automated computer program repair, particularly the obsolescence of manual repairs to software errors and problems. According to the article, automated repair can increase programmer efficiency and output. The article also discusses concepts such as intelligent navigation and symbolic reasoning.